United Nations World Crime Surveys: Fourth Survey, 1986-1990 ([Verlag nicht ermittelbar], 1997)
The Fourth United Nations Survey, covering the years 1986-1990, was designed to increase knowledge regarding the incidence of reported crime and the structure of criminal justice systems, as a basis for improving the international exchange of information. The main objectives of the survey were to determine which data are generally available in national databases and to provide an instrument for strengthening cooperation among member states of the United Nations by putting the review and analysis of national crime-related data in a broader context. Variables describe combined police and prosecution expenditure by year and by country, number of police personnel by gender, total number of homicides by country and by city, number of assaults, rapes, robberies, thefts, burglaries, frauds, and embezzlements, amount of drug crime, number of people formally charged with crime, age of suspects, number and gender of prosecutors, number of individuals prosecuted and the types of crimes prosecuted for, gender and age of individuals prosecuted, types of courts, number of individuals convicted and acquitted, numbers sentenced to capital punishment and to various other punishments, number of convictions on various charges, number of individuals sentenced and in detention, number of prisoners, sentence lengths, and prison demographics.